Israel Update : bulletin of the Society for the Protection of Personal Rights for lesbians, gay men and bisexuals in Israel. (Tel Aviv : SPPR, 1993)
Fonds Suzan Daniel (FSD)
Periodiciteit : maandelijks(?)Redactie : PO Box 37604, 61375 Tel Aviv
Engels
Periodiek